Sex differences in judgement of facial affect: A multivariate analysis of recognition errors - Thayer, Julian; Johnsen, Bjørn Helge (Scandinavian journal of psychology, 2000)
The present paper investigated recognition errors in affective judgement of facial emotional expressions. Twenty‐eight females and sixteen males participated in the study. The results showed that in both males and females emotional displays could be correctly classified, but females had a higher rate of correct classification; males were more likely to have difficulty distinguishing one emotion from another. Females rated emotions identically regardless of whether the emotion was displayed by a male or female face. Furthermore, the two‐factor structure of emotion, based on a valence and an arousal dimension, was only present for female subjects. These results further extend our knowledge about gender differences in affective information processing.